ChemistryOpen
ChemistryOpen is a multidisciplinary, gold-road open-access, international forum for the publication of outstanding Full Papers and Communications from all areas of chemistry and related fields. It is co-owned by 16 continental European Chemical Societies, who have banded together in the alliance called ChemPubSoc Europe for the purpose of publishing high-quality journals in the field of chemistry and its border disciplines. As some of the governments of the countries represented in ChemPubSoc Europe have strongly recommended that the research conducted with their funding is freely accessible for all readers (Open Access), ChemPubSoc Europe was concerned that no journal for which the ethical standards were monitored by a chemical society was available for such papers. ChemistryOpen fills this gap.